Filsafat Kebahagiaan Guru Perspektif al-Ghazali: Studi Kasus di TPQ Jama’atul Huda Kampung Sidamukti Kecamatan Pangalengan Kabupaten Bandung - Hidayah, Yangyang Ageng (Jurnal Riset Agama, 2022)
Spiritualism sees happiness as something immaterial. Associated with the strength of faith in humans, especially for Muslims. This condition can be found in the TPQ Jama'atul Huda Pangalengan, even though the teacher's condition is lacking in material, but they still teach sincerely. The purpose of this study was to determine the views of teacher happiness and al-Ghazali's perspective on teacher happiness. This type of research is quantitative with descriptive phenomenological methods and the philosophy of teacher happiness for a case study at TPQ Jama'atul Huda, Sidamukti village, Pangalengan district, Bandung district. Al-Ghazali's view of happiness is when a person gets a soul, body, from outside and offers it. Happiness is not solely about material things, but happiness when we can have noble morals.